IJSW Vol. 4 No. 2, February 2022 - Suwandani, Anggita; Heryana, Wawan; Nurjanah, Nurjanah (Indonesian Journal of Social Work, 2023)
Indonesia is currently home to nearly 14.000 refugees and asylum seekers. However, Indonesia is not a signatory to the 1951 Refugee Convention and 1967 Refugee Protocol. Hence, the refugee population in Indonesia is dealing with many difficulties and barriers. The biopsychosocial condition is a vital aspect for every human living. Refugee women are no exception. This research intends to take a snapshot of refugee women in Kalideres, West Jakarta, biologically, psychologically, and socially, and how the forced migrant women live in their prolonged state of limbo. This research adopted a qualitative method and used purposive sampling to select the informants. This research consisted of two primary informants and three supporting informants with specific objectives. Data collection techniques used are in-depth interviews, observation, and literature reviews. This research revealed that the biopsychosocial conditions of refugee women in Kalideres are not appropriately met and by-rights, thus affecting their social function in Kalideres, West Jakarta.